If Another Gas Dispute Breaks out between the Ukraine and Russia, Would Europe Now Be Equipped to Deal with It? - Hella Engerer; Manfred Horn; Anne Neumann (Weekly Report, 2010)
In January 2009, the supply of natural gas from Russia via the Ukrainian pipeline system was interrupted for nearly two weeks. Particularly the countries in Southeastern Europe were ill-prepared for such an event. Disputes regarding both the payment of natural gas supplies and transit rights between Russia and Ukraine have recently flared up again, which gives rise to the question of whether the EU is now better prepared if a similar scenario to that of January 2009 were to happen again. A number of measures have been introduced since the beginning of the year aiming to overcome any delivery shortfalls, but only a few of them have actually already been implemented, e.g. the creation of technical requirements to reverse the flow of natural gas. Therefore, supply shortages in some Southeastern European countries can not be fully excluded.
Keywords: N74; 330; Natural gas; Gas storage; Security of supply